2015
DOI: 10.11621/pir.2015.0405
|View full text |Cite
|
Sign up to set email alerts
|

Postnonclassical methodology and application of virtual reality technologies in social research

Abstract: The postnonclassical paradigm has increasingly become a conceptual basis for social research in various fields in an attempt to overcome the limitations of the classical and non-classical approaches. Subjects of social research activities require changes in the paradigm at all levels of research: from the statement of the problem to the elaboration of the appropriate methods and the analysis of the research data. The search for new research methods, technologies and techniques plays a crucial role in this proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Nowak et al [40] reported that the realism of the representation increases the social presence of the interacting person. According to the field of the psychology of perception, individuals inherently prefer anthropomorphic (human-like) representations during interactions, suggesting an innate preference for realism and lifelike interactivity (Zinchenko et al) [41]. This psychological insight reinforces our findings, highlighting the preference for point cloud-centric representations which, due to their increased verisimilitude, fostered a heightened sense of social telepresence, in contrast to their graphical counterparts.…”
Section: Streaming Remote Users With Point Clouds Improves Usability ...supporting
confidence: 82%
“…Nowak et al [40] reported that the realism of the representation increases the social presence of the interacting person. According to the field of the psychology of perception, individuals inherently prefer anthropomorphic (human-like) representations during interactions, suggesting an innate preference for realism and lifelike interactivity (Zinchenko et al) [41]. This psychological insight reinforces our findings, highlighting the preference for point cloud-centric representations which, due to their increased verisimilitude, fostered a heightened sense of social telepresence, in contrast to their graphical counterparts.…”
Section: Streaming Remote Users With Point Clouds Improves Usability ...supporting
confidence: 82%
“…They also make the inclusion of distant participants possible (Fox et al, 2009). Virtual reality (VR) has been used, for instance, for the study of (non-verbal) behaviour, social interaction skills, interpersonal persuasion, social inhibition, social anxiety, prosocial behaviour or prejudice and stereotyping (Fox et al, 2009;Zinchenko et al, 2015). Recently, the first studies have been presented that used machine learning for text analysis in social work.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, digital technologies, particularly virtual reality (VR) systems, are in wide use in the studies of social processes (Zinchenko et al, 2015;Fox et al, 2009;Blascovich et al, 2002). Nonverbal behavior is one of the psychological phenom-ena explored with the help of VR technologies, which were developed in order to study interaction with virtual partners.…”
Section: Introductionmentioning
confidence: 99%